Numerical simulation of fenestrated graft deployment: Anticipation of stent graft and vascular structure adequacy. (5th November 2020) - Dupont, Claire; Kaladji, Adrien; Rochette, Michel; Saudreau, Blandine; Lucas, Antoine; Haigron, Pascal
Abstract: Fenestrated endovascular aneurism repair (FEVAR) is a minimally invasive technique, and its success depends on the adequacy of the correspondence between the visceral arteries ostia and position of the fenestrations of the stent graft (SG) during its deployment in juxtarenal aneurisms. However, the fenestration position is generally determined from a preoperative computerised tomography (CT) scan, without considering the vascular deformation induced by the insertion of the endovascular tools. Catheterisation difficulties may occur during clinical procedures. Accordingly, the objective of this work is to present an initial proof of concept aimed at anticipating and optimising the position of the fenestrations, while considering the vascular deformation induced by the insertion of the endovascular tools. The proposed method relies on the finite element method to simulate the SG deployment in a vascular structure (VS), and considers the vascular deformation induced by the tools. After determining the optimal simulation parameters for a patient‐specific case, the robustness of the method is demonstrated on six other representative anatomies. The simulated SG is also compared with post‐deployment CT observations, and demonstrates good adequacy. The results show that the numerically corrected fenestration positions, as determined from the simulated results following the insertion of the endovascular tools, deviate from those of the standard plan (as determined from the preoperative CT scan). This indicates that the SG–VS adequacy could be improved via simulation‐based planning, to anticipate potential catheterisation difficulties. Abstract :